Soil acidity remediation in sub-Saharan Africa requires targeted investments - Silva, João Vasco; Aramburu Merlos, Fernando; Baudron, Frédéric; Gameda, Samuel; Sida, Tesfaye Shiferaw; Ruganzu, Vicky; Meliyo, Joel; Debello, Moti Jaleta; Chamberlin, Jordan; Hijmans, Robert J. (Springer, 2025)
Acid soils are widespread across sub-Saharan Africa. Agricultural lime can be used to alleviate production constraints associated with soil acidity, but lime is not widely available in the region, and it is unclear if applying it would be profitable. Using lime requirement models and crop yield responses to soil acidity modelled as plateau-linear decay functions, we estimated the profitability of acid soil remediation through liming. Crop yield loss to soil acidity occurs on 32.7 Mha, or 23% of sub-Saharan Africa's cropland. The burden of acid soils is US$6.0 billion (6% of the current production value), and 75% of that could be profitably alleviated. Under prevailing conditions, liming would be profitable in the year of application on 6.2 Mha (with an average profitability of US$278 ha-1) and on 8.8 Mha when lime's long-term effect is considered. Intensification of crop production and lower relative lime/output prices could make liming profitable on more cropland.